Design of Prototype Aircraft Noise Monitoring System Using Microcontroller - Ahmad Ridwan; Triyanto Pangaribowo (International Journal of Advanced Technology in Mechanical, Mechatronics and Materials, 2021)
This paper was presented a design of aircraft noise monitoring system using microcontroller. This system is for monitoring noise levels to make it easier to analyze and measure noise that can be accessed remotely. The measurement results are accessed through a browser with IP address access (Internet Protocol) from the local server esp32 and also OLED 0.96 inc. Taking the noise value for 10 seconds with data samples every 1 second with aircraft noise sources consisting of APU (Auxiliary Power Unit), dual pack on and engine motoring. With each noise value of 61.5 dB, 75.6 dB and 82.5 dB.